More Than Only Skin Deep: Appearance Self-Concept Predicts Most of Secondary School Students’ Self-Esteem - Baudson, Tanja G.; Weber, Kira E.; Freund, Philipp A. (Frontiers in Psychology, 2016)
One important goal of education is to develop students' self-esteem which, in turn, hinges on their self-concept in the academic, physical, and social domains. Prior studies have shown that physical self-concept accounts for most of the variation in self-esteem, with academic and social self-concepts playing a much lesser role. As pressure towards perfection seems to be increasing in education, appearance, and social relationships (three aspects that relate to crucial developmental tasks of adolescence), the goal of the present field study was to examine whether former findings still hold true in the light of the changing societal context. A sample of 2,950 students from a broad range of German secondary schools (47% girls, age 10–19 years) responded to a recently validated German-language questionnaire assessing multiple self-concept facets (Weber & Freund, 2016). We examined which self-concept aspects predict self-esteem best and whether the pattern is comparable across genders and achievement levels using latent regression analyses. Results show that self-concept of appearance is still by far the strongest predictor (total sample: B = 0.77, SE = 0.02, p < .01) and that this is especially the case for girls and students from special educational schools. Other aspects play a much lesser role. The discussion explores why appearance is so neglected, compared to the more academic subjects, and what school can do to account for its vast importance for students' self-esteem.